(3SQ GdCSQGQs - (3eLghds
(3ChdgG (B:s
... (3adeG cGf GdYde CTQa efbHI hCLd eQJHI hCHgi eaNQI hGfaY eJLQI EP Hg jJhSd Edi JhMjO QH GdYGdejf hEdi JUOjb CfHjGFg hGdeQSdjf UdhGJ Gddg Ydjge GLeYjf UGQ GdYdeGA NhGU YHGO Gddg GdPjf GLJHGge Edi eYGde Ojfg (B...s
(3BNQgG (B:s
.... (3abO bGd Cgd GdJUha Cf GdeSGdcI Edi GdCMhGd jZad Yf eMhdgG hbO bGd Gddg JYGdi (B{ (3hdG jCef ecQ Gddg EdG Gdbhe GdNGSQhf (B} (3hdPdc (B.. (3aj MOjK GdbOSj jG eMeO HTQ (B....s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs